Comments on "Zinc supplementation is associated with a reduction in serum markers of inflammation and oxidative stress in adults: A systematic review and meta-analysis of randomized controlled trials". (May 2021) - Jafari, Alireza; Ghobadi, Saeed
Abstract: We carefully read the meta -analysis by Hosseini et al. (1) on the effects of Zinc supplementation on inflammation and oxidative stress markers, which was recently published in Cytokine journal. The authors show that Zinc supplementation significantly decreased CRP, TNF, and MDA while having no significant effect on IL-6. Although respecting the authors' efforts, we are concerned about different aspects of the current review: the inadequate search strategy, the methodological flaws, the interpretation of data, and the reporting of the results that might lead to biased results.